Aplikasi mikrokontroler pada teknologi tepat guna dalam kehidupan sehari-hari - Risgunawati, Amelya Tanjung (Maliki Interdisciplinary Journal, 2024)
In this modern era, technology is widely used to make human work simpler. Everything that is still done manually can now be done automatically, without the need for human intervention. Automatic system design cannot be separated from the role of the microcontroller. A microcontroller is an electronic component that has the main function as the brain or control center of an electronic system. Microcontrollers can be applied in various fields in everyday life. Microcontrollers are widely used for automation. Apart from that, the microcontroller can also be used for remote monitoring. Microcontrollers are widely used because they do not take up much space and are easy to use when paired with a sensor. The development of microcontrollers as an appropriate technology continues to be developed today. Therefore, microcontrollers can be found easily in everyday life, either as a monitoring function or as a control function.